ANALYSIS OF CLEAN WATER ACHIEVEMENTS IN THE NORTH of SURABAYA City ACCORDING TO SDGs - Andrey Ferdian Rumpuin; Rooslan Edy Santosa (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
National Medium-Term Development Plan (RPJMN) targets 100% of the clean water access and sanitation for all Indonesian people, the program is valid for 2015-2019. Research was conducted to measure the RPJMN target achievement . The analysis was taken in North Surabaya city: Bulak and Krembangan Subdistricts, research methods used is by EHRA and the output used qualitative from Microsoft Excel with result reaching 100%. Societies obtained water sources from: bottled water, refilled water, and regional water supply (PDAM). PDAM water is used for dishwashing and brushing teeth, societies consider the water is not feasable. The difficulty level in obtaining clean water is 20.2% due to technical problems. Satisfaction level of PDAM water quality is 82%, while the remaining 18% are not. Occured problems: murky water after pipeline repairs, water clarity, larvae in a reservoir, and others. Societies reproccess the PDAM supply for consumption reaches 93%, it cannot be used directly.